Agricultural mechanization in Africa: Insights from Ghana’s experience - Diao, Xinshen; Silver, Jed; Takeshima, Hiroyuki (International Food Policy Research Institute, 2017)
This brief explores recent developments in Ghana that lend insight into the drivers of mechanization and the appropriate role of government policy in supporting this transition.